Cetacean species richness in relation to anthropogenic impacts and areas of protection in South Africa's mainland Exclusive Economic Zone. (1st November 2020) - Purdon, Jean; Shabangu, Fannie W.; Pienaar, Marc; Somers, Michael J.; Findlay, Ken
Abstract: The world's oceans are subject to the multiple impacts of human activity and to the consequent threats to the health of many and varied ocean ecosystems. Oceans around South Africa are no exception and, with the need for economic growth in the country, anthropogenic stressors on ocean resources are rapidly increasing. In this study, we investigated 14 different anthropogenic stressors that impacted ocean health between 2003 and 2013, and their cumulative anthropogenic effects on cetaceans in the South African Exclusive Economic Zone (EEZ) and South African Marine Protected Areas (MPA), Important Marine Mammal Areas (IMMA), Ecologically or Biologically Significant Areas (EBSA) and ecoregions. We determined cetacean species richness in these five area categories using ensemble models, and identified anthropogenic impacts from relevant literature. We calculated and compared the average species richness, the average trend for each anthropogenic stressor and average cumulative impact between 2003 and 2013 in the five areas. Results highlight that climate related stressors (such as sea surface temperature and ocean acidification), together with shipping stressors, are increasing more rapidly than other stressors across the EEZ. Cetacean species richness was highest along the west coast shelf and shelf edge where sea level rise, ocean acidification, shipping, and commercial pelagic fishing with low by-catch were most pronounced. The results of this study will inform marine spatial planners and policy makers in determining priority areas for cetacean conservation and in identifying anthropogenic stressors that need to be addressed to mitigate cumulative anthropogenic impacts on cetaceans.